ADAPTING THE CULTURAL FORMS IN ARCHITECTURAL DESIGN CONCEPT OF TOURISM CENTRE ON MULES ISLAND, MANGGARAI - Fanggidae, Linda Welmintje; Jerobisonif, Aplimon; Dima, Thomas Kurniawan; Dahoklory, Lodwik Obed; Maromon, Rifat Yoktan Y.; Rudiyanto, Roseven (Jurnal Ilmiah Arsitektur, 2024)
Mules Island, a small island in the Flores archipelago, possesses a diverse array of tourist attractions. Unfortunately, the island, which falls within the settlement area of the Manggarai ethnic group, lacks facilities to support the development of tourism activities. Thus, designing a tourism centre to address these needs is necessary. At the same time, the local community faces challenges related to cultural identity. Mules Island is home to a multi-ethnic population, with no single dominant ethnic group, a condition that raises the risk of cultural assimilation potentially eroding all existing ethnic identities. Preliminary studies indicate that the residents of Mules identify themselves as part of the Manggarai community. Consequently, Manggarai culture is an apt source of inspiration for the architectural design of the proposed tourism center. The design draws inspiration from two Manggarai cultural elements: the traditional Manggarai house known as Mbaru Niang and the distinctive Manggarai rice field pattern referred to as Sawah Lodok. These cultural forms are adapted into the design through a process of form transformation, employing both traditional and borrowing methods. The proposed facilities include a Tourist Information Center, cottages, gazebos, an observation tower, a plaza with food stalls, a plaza with souvenir kiosks, an amphitheater, a prayer room, and public restrooms. All structures incorporate plan and roof forms derived from the transformation of Mbaru Niang, while the site layout reflects the transformed pattern of Sawah Lodok. The architectural design of the tourism center on Mules Island has promoted the identity and the beauty of Manggarai culture while fulfilling its functional role in supporting tourism development activities.